2011
DOI: 10.1186/1750-2187-6-10
|View full text |Cite
|
Sign up to set email alerts
|

G-patch domain and KOW motifs-containing protein, GPKOW; a nuclear RNA-binding protein regulated by protein kinase A

Abstract: BackgroundPost-transcriptional processing of pre-mRNA takes place in several steps and requires involvement of a number of RNA-binding proteins. How pre-mRNA processing is regulated is in large enigmatic. The catalytic (C) subunit of protein kinase A (PKA) is a serine/threonine kinase, which regulates numerous cellular processes including pre-mRNA splicing. Despite that a significant fraction of the C subunit is found in splicing factor compartments in the nucleus, there are no indications of a direct interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Similarly, the KOW motif from the bacterial elongation factor NusG has shown nucleic acid-binding activity and shares stmctural homology with the tudor protein-protein interaction motif (Steiner et al 2002). Whereas MOS2 has not been experimentally shown to bind RNA, the human M0S2 homolog GPKOW binds RNA in a manner dependent on protein kinase A (Aksaas et al 2011). Furthemiore, the remote yeast homolog SPP2 is an essential protein required for the first RNA cleavage step in pre-mRNA splicing.…”
Section: Components Of the Rna Processing Machinery: Mos2 Mos4 And mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the KOW motif from the bacterial elongation factor NusG has shown nucleic acid-binding activity and shares stmctural homology with the tudor protein-protein interaction motif (Steiner et al 2002). Whereas MOS2 has not been experimentally shown to bind RNA, the human M0S2 homolog GPKOW binds RNA in a manner dependent on protein kinase A (Aksaas et al 2011). Furthemiore, the remote yeast homolog SPP2 is an essential protein required for the first RNA cleavage step in pre-mRNA splicing.…”
Section: Components Of the Rna Processing Machinery: Mos2 Mos4 And mentioning
confidence: 99%
“…Although MOS2 has not been shown to directly associate with the MAC, human and yeast homologs of MOS2 have been implicated as components of the conserved splieeosome-assoeiated complex (Roy et al 1995;Bessonov et al 2010;Aksaas et al 2011). Additionally, M0S2 has been shown to be required for proper splicing of SNCI (S Xu and Y Zhang, unpubl.).…”
Section: Components Of the Rna Processing Machinery: Mos2 Mos4 And mentioning
confidence: 99%
“…PKA subunits are encoded by four R and C subunit genes, respectively (RIα, RIIα, RIβ, RIIβ, Cα, Cβ, Cγ and PRKX) [21]. Specificity in the cAMP/PKA signal transduction pathway is obtained by tissue-specific expression and targeting the R subunits to A-kinase anchoring proteins (AKAPs) in the cytosol and targeting of the C subunit to C subunit-binding proteins both in the cytosol and nucleus [22][28]. PKA is activated upon binding of four molecules of cAMP to the R dimer, releasing the C subunits to phosphorylate relevant substrates on serine and threonine residues in its vicinity [29].…”
Section: Introductionmentioning
confidence: 99%
“…MOS2 has homologs in human, mouse, and worm [31,45]. A genome-wide RNAi screen in worm indicated that knock-down of the MOS2 homolog causes embryonic lethality [46].…”
Section: Discussionmentioning
confidence: 99%